Surgical treatment of diaphyseal humeral fractures - Pavlacký, Tomáš; Veselý, Radek; Suchomel, Radomír; Paša, Libor; Sládek, Filip; Pink, Tomáš; Kočiš, Ján (Úrazová chirurgie, 2018)
Introduction: Conservative approach is the golden standard for treatment of diaphyseal humeral fractures, supplemented with plate osteosynthesis in specific indications. However, nail osteosynthesis is becoming more popular in the recent years, namely due to a significant improvement in the areas of surgical techniques and implants used, which have resulted in a decrease of complications. This technique has become the treatment of choice at our centre. Aim: The aim of our work was to assess the success rate of diaphyseal humeral fractures osteosynthesis in a retrospectively evaluated patient population, and also to define the risk factors of potential non-healing. Methods: A total of 167 patients who were operated at the Trauma Hospital of Brno between 2011 and 2016 were enrolled into the retrospective clinical trial with 3rd degree quality evidence. The assessed parameters included the outcome of healing and the number of complications, such as paresis of n. radialis, prolonged healing or incidence of non-unions. Furthermore, we assessed in more detail a group of 17 patients with a diagnosed non-union, and concentrated upon possible predisposing factors. Results: We identified a total of 9 (5.4 %) patients with the complication of postoperative paresis of n. radialis. Six of these patients were operated using nail osteosynthesis; plate osteosynthesis was used in the remaining three patients. We also observed 10 patients (6.0 %) who manifested signs of prolonged healing, and a total of 17 (10.2 %) patients in whom the definition of non-union was confirmed on radiography examination. Of these patients, 15 (12.2 %) were operated using the nailing technique (12.2 %); two patients were treated with plates (5.6 %). The performed analysis of these patients revealed that the profile patient with a predisposition for occurrence of a non-union is a female in the seventh decade of her life, with a fracture in the middle third of the diaphysis, type A1 or B1 according to AO, with type 2 diabetes mellitus, and body weight on the border of obesity. None of the other observed factors has been proven significant. Conclusion: Plate osteosynthesis and intramedullary nailing for the treatment of diaphyseal humeral fractures present fully-fledged alternatives to the conservative approach. According to current literature, there exist no significant differences when comparing these techniques as far as the success rate of healing is concerned, although our experience suggests slightly better outcomes on radiography in patients treated with plate osteosynthesis, and a smaller incidence of n. radialis injury associated with the nailing technique.